RNA interference shows that Spook, the precursor gene of 20-hydroxyecdysone (20E), regulates the molting of Macrobrachium nipponense. Issue 213 (October 2021) - Yuan, Huwei; Qiao, Hui; Fu, Yin; Fu, Hongtuo; Zhang, Wenyi; Jin, Shubo; Gong, Yongsheng; Jiang, Sufei; Xiong, Yiwei; Hu, Yuning; Wu, Yan
Highlights: Complete Mn-Spook gene was cloned and identified from the ovary of M. nipponense for the first time. qRT-PCR, ISH, RNAi, ELISA and other techniques were used to systematically analyze Mn-spook gene. Mn-Spook played a pivotal role in the molting of M. nipponense by participating in 20E production. Abstract: The aim of this study was to explore the function of the Mn-Spook gene, which was found in the ovary transcriptome of the Oriental river prawn ( Macrobrachium nipponense ). The Spook gene, which is the precursor gene of 20-hydroxyecdysone (20E), plays an important role in the process of molting in many arthropods, but its function in M. nipponense is unclear. We cloned the full-length Mn-Spook gene from the ovary of M. nipponense and found that it had the same conserved domains as the P450 gene of the Halloween family of genes. The Mn-Spook gene was highly expressed in ovary and gill tissue during the breeding period. During ovarian development, Mn-spook gene expression was highest at the nearly-ripe stage, and it also was highly expressed in the zoea developmental stage. Cellular localization analysis showed that Mn-Spook signals accumulated in the cytoplasmic membrane and nucleus of oocytes. Finally, we used RNA interference to evaluate the function of the Mn-Spook gene. Compared with the control group, in vivo injection of Mn-Spook dsRNA effectively downregulated the expression of Mn-Spook and the content of 20E. The molting frequency of M. nipponense in the experimental group also was significantly inhibited. These results demonstrated that the Mn-Spook gene played an important role in the molting process of M. nipponense .